1998
DOI: 10.1515/cclm.1998.153
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of Eleven Combined Oral Contraceptives on Serum Triglycerides, γ-Glutamyltransferase, Alkaline Phosphatase, Bilirubin and other Biochemical Variables

Abstract: The objectives of this paper are to update and quantify the biological effects of the most commonly used oral contraceptives (OC) on 15 biochemical tests currently determined in clinical laboratories and to compare these effects between the different types of OC. The sample population was constituted by 1604 women using combined OCs and the control group comprised 3466 women in the same age range not taking medication. Women taking OC were divided into 11 groups according to the estrogen/progestogen combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 15 publications
1
14
2
Order By: Relevance
“…Steroid hormones have been reported to increase aminotransferases among OC users [48,49]. In our earlier study with triglycerides, HDL and LDL, the level of serum markers were found to be high among users [50]. Thus, it is concluded that the intake of OC affects the level of various blood serum enzymes and it may depends on the estrogens and progestin dosage or the androgenic activity of the progestin [51].…”
Section: Discussionmentioning
confidence: 99%
“…Steroid hormones have been reported to increase aminotransferases among OC users [48,49]. In our earlier study with triglycerides, HDL and LDL, the level of serum markers were found to be high among users [50]. Thus, it is concluded that the intake of OC affects the level of various blood serum enzymes and it may depends on the estrogens and progestin dosage or the androgenic activity of the progestin [51].…”
Section: Discussionmentioning
confidence: 99%
“…Oral contraceptives have also demonstrated efficacy in preventing dysfunctional bleeding, but their effect on acne or hirsutism is variable, as well as on lipid and carbohydrate metabolism 21,22 . Our special interest in the oral contraceptive combination of EE/CPA lies in the antiandrogenic properties of cyproterone acetate, since the negative effects of progestins on lipid and carbohydrate metabolism are related to their androgenic potency 21,22 .…”
Section: Correlation Studiesmentioning
confidence: 99%
“…Our special interest in the oral contraceptive combination of EE/CPA lies in the antiandrogenic properties of cyproterone acetate, since the negative effects of progestins on lipid and carbohydrate metabolism are related to their androgenic potency 21,22 .…”
Section: Correlation Studiesmentioning
confidence: 99%
See 2 more Smart Citations